Victim Arrest in Intimate Partner Violence Incidents: A Multilevel Test of Black’s Theory of Law - Lisa Holland-Davis; Jason Davis (Journal of Public and Professional Sociology, 2014)
Mandatory and preferred arrest policies were heralded as major advances in protecting victim rights in cases of intimate partner violence. Soon after these policies were implemented, researchers began to document a disturbing rise in the number of victims arrested in these incidents. This paper applies Black’s theory of the behavior of law to victim arrest in intimate partner violence incidents in order to identify the structural and individual statuses that increase the likelihood of victim arrest. Data from the 2004 National Incident Based Reporting System, 2000 decennial Census, and 2000 Law Enforcement Management and Administrative Statistics report are analyzed using multilevel modeling to offer a multi-level test of Black’s theory. Findings suggest moderate support for Black’s theory. Measures of stratification, morphology, culture, organization, and respectability significantly influence the likelihood a victim will be arrested. Implications for policy and directions for future research are addressed.